THE DIVERSITY OF EVERYDAY EXPERIENCES OF FAMILIES AND CHILDREN WITH DIGITAL TECHNOLOGIES - Vitorino Sampaio, Ines; Bandara, Dinusha; Pangrazio, Luci; Marôpo, Lidia; Jorge, Ana; Sibak, Andra (AoIR Selected Papers of Internet Research, 2026)
This panel examines how parents and carers make decisions about the access and use of digital technologies by their young children. With many family practices now mediatized, it explores the conditions under which family members (re)negotiate their understandings about their children’s relationship with technology and the tensions that emerge. The panel combines five papers which focus on the diversity of daily digital experiences of families and children in Australia, Brazil, Portugal and Estonia. The papers use diverse theoretical and methodological approaches such as: the technological, legal and economic analysis of apps, participant observation, thematic analysis of interviews, and multimodal content analysis. They draw on case studies, critical data studies and migration studies to unpack the diverse and divergent practices and understandings families have of digital technologies worldwide. The papers are titled: ‘Parental Approaches to Children’s Access and Use of Technologies: A Case Study of an Indigenous Community in Brazil’; ‘How Melbourne- Based Sri Lankan Australian Families Use Digital Technology in Everyday Family Routines’; ‘Australian Families in the EdTech Data Assemblage: The Case of Storypark; ‘The Playbour of Children of Influencer Moms in Brazil and Portugal’ and ‘Plataforms as the Materialitis of Care: Experiences and Practices of Three-Generational Families from Estonia’. Together, the papers identify crucial challenges for parents to protect and promote the rights of their children in this complex and evolving digital environment. Some of these challenges are common to all papers, but others are substantially different, particularly when contrasting case studies in the Global North and Global South.